Diagnostic Performance and Advanced Imaging Reduction With Digital Tomosynthesis in Scaphoid Fracture Management. (November 2022) - Perloff, Eric; Cole, Keegan; Sternbach, Sarah; Rosenbaum, Andrew; Quinn, David
Background: Management of scaphoid fractures often requires advanced imaging to achieve accurate diagnoses and appropriate treatment. Digital tomosynthesis (DTS) is a cross-sectional imaging modality that may be used to substitute magnetic resonance imaging or computed tomographic scans. The purpose of this study is to: (1) determine the diagnostic accuracy of DTS in occult scaphoid fractures; and (2) report on the reduction of other advanced imaging when using DTS. Methods: From May 2014 to October 2017, the charts of all patients who underwent scaphoid tomogram were retrospectively reviewed. The diagnostic accuracy of DTS for occult fracture was compared with 2-week follow-up plain films. To measure the reduction in utilization of advanced imaging, it was determined whether DTS eliminated the need for advanced imaging by providing adequate information regarding the clinical question. Results: A total of 78 patients underwent scaphoid tomography in this time frame: 39 for occult fracture, 33 for fracture union, 5 for fracture morphology, and 1 for hardware positioning. For the detection of occult fracture, DTS had a sensitivity of 100%, specificity of 83%, positive predictive value of 64%, and negative predictive value of 100%. Advanced imaging was not used in 35 of the remaining 39 patients based on the results obtained by DTS. In patients who did receive advanced imaging, 83% of tomograms provided conclusive diagnostic information. Conclusions: Digital tomosynthesis increases the diagnostic sensitivity of occult scaphoid fractures, reducing unnecessary immobilization and advanced imaging. Digital tomosynthesis provides clinical detail beyond plain film, which reduces the need to obtain advanced imaging when assessing union, fracture pattern, and hardware placement.